POJOK BACA (BALANCE CAIRAN) UNTUK SURVIVOR HEMODIALISIS - Eska Dwi Prajayanti (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Background: Management of end-stage renal failure patients one of the treatments is hemodialysis. Complications that arise with respect to fluid overload in patients with kidney failure can be prevented through effective and efficient fluid intake restrictions. Efforts to create restrictions on fluid intake in patients with kidney failure can be done through monitoring fluid intake per day. Fluid restriction program in patients in order to prevent complications and maintain quality of life, it is necessary to analyze practices related to intervention in controlling the amount of fluid intake through recording the amount of fluid taken and urine released every day. Pojok Balance Cairan (BACA) is one way to help hemodialysis patients learn how to calculate fluid needs in their body and help determine dietary settings for hemodialysis patients where in the reading corner will be explained related to how to calculate fluid balance and how the right diet in patients hemodialysis according to the severity of the disease. Method of implementation: lectures and demonstrations. Conclusion: POJOK BACA can prolong the life of patients undergoing hemodialysis because it can reduce the risk of complications that arise such as shortness of breath.Keywords: Hemodialysis, Liquid, Pojok Baca